2020
DOI: 10.1108/imefm-12-2018-0440
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of perceived quality of self-service banking on customer satisfaction

Abstract: Purpose This study aims to measure the effect of customers’ technology readiness and the quality of electronic services on customer satisfaction. Design/methodology/approach The statistical sample included 410 respondents from 24 branches of a private bank. The sampling method was questionnaire. Because of the structural and organizational similarity of private banks and the elimination of nuisance variables, a bank with the most branches and customers has been selected. To test the model, equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 58 publications
8
49
0
5
Order By: Relevance
“…Results revealed that payments, compliance services, and advisory of Fintech influence the customers' retention while financing service has no significant impact on customer retention. Moreover, Pooya, Khorasani, and Ghouzhdi (2020) measured the impact of technology readiness and the quality of e‐services on customer satisfaction. A questionnaire was designed to collect data from a sample that included 410 customers.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Results revealed that payments, compliance services, and advisory of Fintech influence the customers' retention while financing service has no significant impact on customer retention. Moreover, Pooya, Khorasani, and Ghouzhdi (2020) measured the impact of technology readiness and the quality of e‐services on customer satisfaction. A questionnaire was designed to collect data from a sample that included 410 customers.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Banks and nations should utilize Digital Financial Inclusion (DFI) to maintain banking stability to reduce the crisis of liquidity (Banna and Alam, 2021). Further, technological readiness has a significant positive impact on client satisfaction in terms of self-service (Pooya et al, 2020). The introduction of compassionate policies might help to prevent stress, absenteeism, decrease productivity and encourage the morale of the employees (Oruh et al, 2021).…”
Section: Efforts Of the Banksmentioning
confidence: 99%
“…While customers look for satisfaction, the usually opt for portability versus reliability when choosing a platform to access internet services (Al-Khalaf & Choe, 2020) even when it can be reasoned that reliability possesses the utmost essential features of internet banking. Customer satisfaction and quality are very parallel in the banking sector most especially because banking is in the service industry (Pooya, Khorasani & Ghouzdhi, 2020;Tseng & Wei, 2020). Accordingly, quality is measured by the consumer who might appreciate quality of service beyond quality of information or quality of the system (Fornelle, 1992).…”
Section: Customer Satisfaction (Cs) and Adoption Of Online Banking As A Mediatormentioning
confidence: 99%